Comparing written and voice captured responses of the user experience questionnaire (UEQ) - Mata Serrano, Jean Carlo (2022)
Standardized questionnaires are widely used instruments to evaluate UX and their capture mechanism has been implemented in written form, either on paper or in digital format. This study aims to determine if the UX evaluations obtained in the standardized UEQ questionnaire (User Experience Questionnaire) are equivalent if the response capture mechanism is implemented using the traditional written form (digitally) or if a conversational voice interface is used. Having a UX evaluation questionnaire whose capture mechanism is implemented by voice could provide an alternative to collect user responses, preserving the advantages present in standardized questionnaires (quantitative results, statistically validated, self-reported by users) and adding the ease of use and growing adoption of conversational voice interfaces. The results of the case study described in this paper show that, with an adequate number of participants, there are no significant differences in the results of the six scales that make up UEQ when using either of the two response capture mechanisms.